Cervical vestibular evoked myogenic potentials in children - Pereira,Alcione Botelho (2015)
INTRODUCTION: Cervical vestibular evoked myogenic potential is a test used in neurotological examination. It verifies the integrity of vestibular function through a muscular response evoked by an acoustic stimulation which activates the saccular macula. Normal standards in adults have been established, however, there are few published data on the normal responses in children.OBJECTIVE: To establish normal standards for vestibular myogenic responses in children without neurotological complaints.METHODS: This study's design is a cohort with cross-sectional analysis. The sample consisted of 30 subjects, 15 females (50%) and 15 males (50%).RESULTS: The age of the subjects ranged between 8 and 13 years, with a mean of 10.2 (± 1.7). P1 peak showed an average latency of 17.26 (± 1.78) ms and a mean amplitude of 49.34 (± 23.07) µV, and the N2 peak showed an average latency of 24.78 (± 2.18) ms and mean amplitude of 66.23 (± 36.18) µV. P1-N2 mean amplitude was 115.6 (± 55.7) µV. There were no statistically significant differences when comparing by gender or by laterality.CONCLUSION: We established normal values of cervical myogenic vestibular responses in children between 8 and 13 years without neurotological complaints.